Moderating role of ethical climates on HRM practices and organizational performance: a proposed conceptual model - Sabiu, Malam Salihu; Tang, Swee Mei; Joarder, Mohd Hasanur Raihan (MCSER Publishing, Rome-Italy, 2015)
Based on the Resource Based View (RBV) perspective, HRM practices are the best way of utilizing vital internal resources that influence performance in organization. Some scholars used individual practice while others used bundles.Despite these studies, however, previous studies have attempted to consider the influence of HRM practices on organizational performance.Some of the studies, have reported mixed findings; therefore, a moderating variable is suggested. This paper proposes ethical climates (EC) as potential moderator on the relationship between HRM practices and organizational performance to enhance the relationship.